2016
DOI: 10.1038/nrm.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into selective autophagy pathways: lessons from yeast

Abstract: Autophagy has burgeoned rapidly as a field of study because of its evolutionary conservation, the diversity of intracellular cargoes degraded and recycled by this machinery the mechanisms involved, as well as its physiological relevance to human health and disease. This self-eating process was initially viewed as a non-selective mechanism used by eukaryotic cells to degrade and recycle macromolecules in response to stress; we now know that various cellular constituents, as well as pathogens, can also undergo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
303
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(319 citation statements)
references
References 171 publications
2
303
0
3
Order By: Relevance
“…Similarly, a typical inducer of bulk autophagy in yeast cells, nitrogen starvation, stimulates preferential degradation of the acetaldehyde dehydrogenase ALd6P, whose enzymatic activity would otherwise reduce cell viability under such conditions (Onodera & Ohsumi, 2004). A growing number of discovered receptors/adaptors for selective autophagy points to the complexity of autophagy selectivity, which originally might have been viewed as lacking selectivity (Dengjel et al, 2012;Mancias et al, 2014;Farre & Subramani, 2016), and also indicates that selectivity of autophagy is most probably determined at the cargo recruitment stage.…”
Section: Sharing Tasks: the Ups-autophagy Interfacementioning
confidence: 99%
“…Similarly, a typical inducer of bulk autophagy in yeast cells, nitrogen starvation, stimulates preferential degradation of the acetaldehyde dehydrogenase ALd6P, whose enzymatic activity would otherwise reduce cell viability under such conditions (Onodera & Ohsumi, 2004). A growing number of discovered receptors/adaptors for selective autophagy points to the complexity of autophagy selectivity, which originally might have been viewed as lacking selectivity (Dengjel et al, 2012;Mancias et al, 2014;Farre & Subramani, 2016), and also indicates that selectivity of autophagy is most probably determined at the cargo recruitment stage.…”
Section: Sharing Tasks: the Ups-autophagy Interfacementioning
confidence: 99%
“…15 A number of other forms of selective autophagy have been described including degradation of ribosomes (ribophagy), peroxisomes (pexophagy), mitochondria (mitophagy), and ER (reticulophagy). 23 However, the molecular mechanisms that regulate many of these processes have not been well characterized for mammalian cells and, thus, have not been investigated during viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, of the ATG transcripts that were examined in this study, dhh1Δ cells demonstrated significantly increased levels of ATG3, 7,8,19,20,22 and 24 mRNA under nutrient-replete conditions (96). In the dcp2-7Δ ts strain, transcript levels for ATG1 through ATG9, ATG11, ATG13 through ATG24, ATG29, 31, 32 and 34 were significantly upregulated in rich conditions (96).…”
Section: Dcp2 and Rck Family Rna Helicases Dhh1/vad1/ddx6mentioning
confidence: 99%
“…At least in yeast, the receptors utilized to target cargos are unique to the form of selective autophagy that the cell is undergoing (5,7,8,21). For further discussion on the topic of selective autophagy, see refs, (22,23).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation